2021
DOI: 10.3390/v13050935
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Evolution of the Molecular Fitness of SARS-CoV-2 Variants: Introducing SpikePro

Abstract: The understanding of the molecular mechanisms driving the fitness of the SARS-CoV-2 virus and its mutational evolution is still a critical issue. We built a simplified computational model, called SpikePro, to predict the SARS-CoV-2 fitness from the amino acid sequence and structure of the spike protein. It contains three contributions: the inter-human transmissibility of the virus predicted from the stability of the spike protein, the infectivity computed in terms of the affinity of the spike protein for the A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…We have demonstrated that, individually, some mutations may stabilize or destabilize the protein structure, since their occurrence triggers different effects on energy balances and potentially affects viral fitness. As shown by the result of our majority consensus analysis and demonstrated by Pucci and Rooman (2021) (138, 484, 614, 681, 845, and 1,176).…”
Section: Discussionsupporting
confidence: 52%
“…We have demonstrated that, individually, some mutations may stabilize or destabilize the protein structure, since their occurrence triggers different effects on energy balances and potentially affects viral fitness. As shown by the result of our majority consensus analysis and demonstrated by Pucci and Rooman (2021) (138, 484, 614, 681, 845, and 1,176).…”
Section: Discussionsupporting
confidence: 52%
“…In addition, with the right computational resources, the presented pipeline can be employed for building a library of all the possible RBD variants, which might be predicted based on solid evolutionary tools [ 114 116 ] and population genetics tools [ 117 , 118 ], for trying to understand which (and where) future spike variants will appear [ 2 , 5 , 16 ], to quickly predict their binding affinity for the different known ACE2 variants present in the world population (i.e., see https://gnomad.broadinstitute.org/gene/ENSG00000130234?dataset=exac ). Thus, it would be possible to early predict which RBD variants might be more dangerous for human health even before their appearance.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…At present, it remains challenging to computationally predict the emergence of future clinically significant SARS-CoV-2 variants, but a couple of approaches have been developed to model the interaction between newly identified SARS-CoV-2 variants and their host and predict their infectivity. A computational pipeline “SpikePro”, consisting of three-step in silico mutagenesis experiments, calculates the stability of mutant spike protein, the binding affinity between mutant spike and human ACE2, and the binding affinity between mutant spike and neutralizing antibodies to predict viral fitness ( Pucci and Rooman, 2021 ). Another recently published work also established a neural network model that could predict binding affinity changes of spike mutations to human ACE2 ( Chen et al, 2021 ).…”
Section: Disease Predictionmentioning
confidence: 99%